2008
DOI: 10.1186/1471-2180-8-73
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a 70-mer oligonucleotide microarray for genotyping of Campylobacter jejuni

Abstract: BackgroundCampylobacter jejuni is widespread in the environment and is the major cause of bacterial gastroenteritis in humans. In the present study we use microarray-based comparative genomic hybridizations (CGH), pulsed-field gel electrophoresis (PFGE) and multilocus sequence typing (MLST) to analyze closely related C. jejuni isolates from chicken and human infection.ResultsWith the exception of one isolate, the microarray data clusters the isolates according to the five groups determined by PFGE. In contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…A number of studies have demonstrated the potential of the high-resolution subtyping of Campylobacter using comparative genomics and its potential application in the context of molecular epidemiology or population surveys (28,38,50,51). Despite these advances, the past decade has seen very limited transfer of genomic approaches to subtyping beyond proof-of-concept studies.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated the potential of the high-resolution subtyping of Campylobacter using comparative genomics and its potential application in the context of molecular epidemiology or population surveys (28,38,50,51). Despite these advances, the past decade has seen very limited transfer of genomic approaches to subtyping beyond proof-of-concept studies.…”
Section: Discussionmentioning
confidence: 99%
“…Within these groups of variable genes, all or a portion of 17 of the 18 intraspecies hypervariable regions published by Parker et al (2006) were identified; region 18 (CJE0944-CJE0947) was absent in our analysis. Portions of two additional recently reported (Rodin et al, 2008) variable regions (regions 19 and 21) were also among the variable genes in our data.…”
Section: Cgimentioning
confidence: 62%
“…A specific pattern of array spots will fluoresce, which is then used to infer the genetic makeup in the test sample [170]. Microarray analysis is an emerging technology that has the potential to become a leading trend in bacterial identification in the dairy and overall in the in food and drink industry, allowing both the detection and/or genotyping of pathogenic microorganisms [171][172][173][174][175][176][177][178][179].…”
Section: Biosensors Microarrays Micro and Nano Electro-mechanical-smentioning
confidence: 99%